Optical Sensing Material Based on p-Toluidine Immobilised in Polyvinyl Alcohol (PVA) Film for Detection of Hydroxymethylfurfural (HMF) in Honey - Mashri Ahmed Yahia; Che Wan Zanariah Che Wan Ngah; Musa Ahmad; Lee Yook Heng (Malaysian Institute of Chemistry, 2025)
Indexed by Scopus